2009
DOI: 10.1111/j.1944-9720.2009.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhetorical Strategies in Chinese and English: A Comparison of L1 Composition Textbooks

Abstract: The present study compared the rhetorical strategies for argumentative writing in Chinese and English composition textbooks. The textbooks were selected based on four criteria. The results of the study revealed that there are similarities and differences in Chinese and English argumentative writing. Both Chinese and English agree upon the function of the argumentative writing, encourage writers to voice their personal opinions, adopt a similar macrostructure for argumentative writing, recommend placing the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Liu (2005), by conducting a comparative analysis of selected online instructional materials on argumentative writing, found that American writers see the imperative to accommodate the readers and attend to their opposition. Resonant with this finding, Liao and Chen (2009) also demonstrated that all English texts, in their samples, attach much importance to addressing opposing viewpoints in argumentative texts. Hence, it can be concluded that Anglo-American scholars take advantage of hedging devices of various types to display the cautiousness and circumspection towards their arguments on the one hand, and to express humility and respect for the readers on the other hand in their argumentative writings.…”
Section: Cultural Influencesmentioning
confidence: 93%
“…Liu (2005), by conducting a comparative analysis of selected online instructional materials on argumentative writing, found that American writers see the imperative to accommodate the readers and attend to their opposition. Resonant with this finding, Liao and Chen (2009) also demonstrated that all English texts, in their samples, attach much importance to addressing opposing viewpoints in argumentative texts. Hence, it can be concluded that Anglo-American scholars take advantage of hedging devices of various types to display the cautiousness and circumspection towards their arguments on the one hand, and to express humility and respect for the readers on the other hand in their argumentative writings.…”
Section: Cultural Influencesmentioning
confidence: 93%
“…Moreover, recent research has suggested the Chinese education system entails rote learning and is geared towards social control and prescribed moral judgments (Kan, 2010). For instance, Liao and Chen (2009) found that argumentative writing is taught differently in Chinese (Hong Kong) schools whereby Chinese textbooks appeal highly to historical and moral issues, while English textbooks suggest using Toulmin's reasoning system. Xiao and Tong (2010) indicated that there has been a recent swing away from the educational emphasis on rationality following the establishment of New China.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared Chinese and Western students' thinking styles (e.g., Heffernan et al, 2010;Jones, 2005;Koh, 2002;Liao & Chen, 2009;Pearce & Zeng, 2007;Ryan & Kam, 2007;Tümkaya et al, 2009;van der Walt, 2010;Yang & Wen, 2004;Yun, 2010). Yet these studies have focused on teaching styles or student-teacher relationships, and no studies have focused on demonstrating how Yin-Yang thinking compares to Western thinking (Liao & Chen, 2009;Liu, 2005;Yang & Wen, 2004).…”
Section: Yin-yang and Paradoxmentioning
confidence: 99%
“…However, there are inadequacies in their studies. For example, Liao and Chen (2009) and Kubota and Shi (2005) fail to provide supporting evidence from the Chinese students' actual texts. The "gap between the instruction and the actual texts suggests a need for further investigation in the future" (Kubota & Shi, 2005, p. 123).…”
Section: Introductionmentioning
confidence: 97%